GAMBARAN PELAKSANAAN INDIKATOR MUTU NASIONAL DI RUANG RAWAT INAP RSUD KABUPATEN MAJENE - irfan irfan ners; Weny Anggraini Adhisty; Indrawati Indrawati; Muhammad Salim Pahmi (Jurnal Kesehatan Marendeng, 2022)
Abstract. National Quality Indicators of Health Services, hereinafter referred to as Quality Indicators, are benchmarks used to assess the level of success of the quality of health services in health care facilities. Purpose: this study aims to find out the description of the Implementation of National Quality Indicators in the Inpatient Room of the Majene District Hospital which is directly related to the role of nurses. Sample: totaling 117 respondents using Stratified Random Sampling. Design: namely a quantitative descriptive research design that aims to describe or describe the variables studied without analyzing the relationship between variables and presented in a descriptive form, which is used to describe the implementation of the National Quality Indicators in the Inpatient Room of RSUD Majene. Results: hand hygiene compliance (70.9%), PPE use compliance (76.1%), patient identification compliance (78.6%) and patient fall risk prevention compliance (72.6%). Conclusion: shows the level of compliance with the implementation of the National Quality Indicators in the Inpatient Room of RSUD Majene which is directly related to the role of nurses who have not complied because they did not reach the target level of compliance according to compliance standards from the Ministry of Health. Abstrak. Indikator Mutu Nasional Pelayanan Kesehatan yang selanjutnya disebut Indikator Mutu adalah tolok ukur yang digunakan untuk menilai tingkat keberhasilan mutu pelayanan kesehatan di fasilitas pelayanan kesehatan. Tujuan: penelitian ini bertujuan untuk mengetahui gambaran Pelaksanaan Indikator Mutu Nasional di Ruang Rawat Inap RSUD Kabupaten Majene yang berhubungan langsung dengan peran perawat. Sampel: berjumlah 117 responden dengan menggunakan Stratified Random Sampling. Desain: yaitu desain penelitian deskriptif kuantitatif yang bertujuan untuk menggambarkan atau memaparkan variabel-variabel yang diteliti tanpa menganalisis hubungan antar variabel dan disajikan dalam bentuk deskriptif, yang digunakan untuk mengetahui gambaran pelaksanaan Indikator Mutu Nasional di Ruang Rawat Inap RSUD Kabupaten Majene. Hasil: didapatkan kepatuhan kebersihan tangan (70,9%), kepatuhan penggunaan APD (76,1%), kepatuhan identifikasi pasien (78,6%) dan kepatuhan upaya pencegahan resiko pasien jatuh (72,6%). Kesimpulan: menunjukan tingkat kepatuhan pelaksanaan Indikator Mutu Nasional di Ruang Rawat Inap RSUD kabupaten Majene yang berhubungan langsung dengan peran perawat belum patuh karna tidak mencapai target tingkat kepatuhan sesuai standar dari Kemenkes.